Public Transport Services and Its Interplay with Users Subjective Well Being (Case Study: Palembang City) - Tsany, M Fairuz; Basrum, Revasari Puspita; Azhar, Muhammad Yusrizal; Ichsan, Fachrully (Universitas Islam Sultan Agung Semarang, 2025)
Cities in Indonesia continue to grow alongside increasing urban populations and urbanisation. A city is considered metropolitan if it has a population of over one million and its economy is dominated by mixed activities such as industry, trade, and services. The development of Palembang into one of Indonesia's metropolitan cities is driven by significant population growth, urbanisation, and the expansion of industrial centres. This growth has led to urban challenges, including a rise in motorised vehicles, resulting in traffic congestion. Residents of Palembang rely on transportation to reach their daily activities, with one of the primary modes being the BRT Transmusi. Theoretically, since commuting is a daily activity, subjective well-being (SWB) is linked to the quality of the transportation mode used daily. User satisfaction is generally influenced by their experience with public transportation. Understanding the interplay between service quality and SWB is important for improving community quality of life. This study examines the interplay between public transport service quality attributes and Transmusi BRT users' SWB. The interplay is measured using Structural Equation Modeling (SEM) with 4 variables and 23 indicators tested. A sample of 384 respondents was used. The findings reveal that bus physical conditions, driver service quality, and service provider empathy significantly positively influence user satisfaction. Furthermore, user satisfaction positively impacts life satisfaction. Public transport service quality attributes also indirectly and significantly affect the life satisfaction of BRT Transmusi users. These findings provide comprehensive insights that can be utilised to enhance public transport services in Palembang.